PENGARUH PROSES PELAKSANAAN KEGIATAN INTI TERHADAP PEMBELAJARAN SOSIOLOGI DI SMA KARTIKA 1-5 PADANG - Yanti, Novri; Husnita, Liza; Erningsih, Erningsih (Pendidikan Sosiologi, 2013)
Background taken this problems bacause the learning of teachers only implement elabotarion activities alone moderate exploration activities and confirmation is often not implemented. One for students can understand on learning materials is to carry out the core activities consisting of exploration, elaboration and konfirmation. The aims of this study to know describe the influence of process implementation of the core activities of teaching sociology at SMA Kartika 1-5 Padang. This type of research is ex post facto, the study subjects were taken proportional random sampling. The population in this study were all students of class XI IPS consists of 4 classes. The sampling technique is done randomly, which was selected as the sample class is class XI IPS 1 and IPS 2.Â The instrument used in this study was a questionnaire using a Likert scale form. The data analysis technique used in this study were student activity that has been modified to be observed student activity. Assessment results of this study were students of the core activities undertaken by teachers is very influential because most students rated the highest at 51,25%, while the lowest at 23,75%. For teachers, the core activities affect learning in high school sociology Kartika 1-5 Padang, due to the influence of the highest value of 100%, while the lowest value of 20%.